Implementasi Kebijakan Partisipasi Anak melalui Pengembangan Forum Anak di Kabupaten Bogor - Anggin Nuzula Rahma; Mala Sondang Silitonga; Ridwan Rajab (Syntax Literate, 2023)
Children's participation in development is one of the important issues in realizing children's rights-based development. Since 2010 until now, the Ministry of Women's Empowerment and Child Protection has initiated a Child Participation Policy through the Development of Children's Forums. This research focuses on seeing the extent to which children's involvement/participation in the development process through the Children's Forum in Bogor Regency as Pioneers and Reporters is not yet optimal using a descriptive qualitative approach. Data collection techniques were carried out using interviews, observation and document review. In determining informants, researchers used a purposive sampling technique. The research results show that not all aspects of the implementation of Riant Nugroho's policy as a measure of success have been fulfilled, such as the aspects of target accuracy, environmental accuracy and process accuracy. The recommendations given are increasing the capacity and quantity of human resources which can be done by means of Convention on The Rights of the Child (KHA) Technical Guidance and Child Protection Policy, to increase the quantity can be done by building networks across regional apparatus and NGO. Regarding budget needs, the Department needs to map needs related to work programs to support child participation policies.